2022
DOI: 10.34190/iccws.17.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Purpose Cyber Environment for Maritime Sector

Abstract: The cyber attack surface in a maritime environment is constantly growing. More current information and computer technologies are being used on cargo and passenger ships to save on operational costs and increase navigational safety. Along with the growing reliance on automation, the risk of a disruption to a vessel's critical systems by drawing on the wrong inputs from sensors to change the behaviour of the actuators has significantly increased. Traditional operational technological systems are much more compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Recent research has demonstrated the potential of AI to improve threat detection and incident response. However, most of these works focus on the application of AI for operating systems and rather than on human training [24]. Our initiative differentiates itself by using AI not only as a cyber defense tool but also to improve the training and preparation of cybersecurity professionals.…”
Section: Review Of Similar Workmentioning
confidence: 99%
“…Recent research has demonstrated the potential of AI to improve threat detection and incident response. However, most of these works focus on the application of AI for operating systems and rather than on human training [24]. Our initiative differentiates itself by using AI not only as a cyber defense tool but also to improve the training and preparation of cybersecurity professionals.…”
Section: Review Of Similar Workmentioning
confidence: 99%